RATING THE ACTIVITIES OF EXECUTIVE AUTHORITIES BY THE PUBLIC - N. N. Chalenko; K. I. Solodovnikova (Финансы: теория и практика)
A social research to assess the maturity and effectiveness of the anti-corruption policy of executive bodies through self-report questionnaires has been carried out. Population: adults (18 years and older). The process of completing and submitting questionnaires (on the condition of anonymity) was not controlled by the researchers. Questionnaires that were not filled out or partially filled out were not accepted. The total sample amount was 320 respondents of which 300 respondents were finally subjected to the study. The social research from the development of questionnaires to the final report was carried out step by step from March 26 to July 20, 2016. The findings of the research were reflected in the State Assignment report of 2016. The polling data was processed using the method of public perception ratings. The public assessment of the effectiveness of anti-corruption policies at various government levels again revealed the confidence of the respondents in the federal authorities. The study resulted in the formation of the perception rating of maturity and effectiveness of individual executive authorities at the public level.